Development and validation of a quantitative PCR assay method of assessing relative resistance of oat (Avena sativa) to crown rust (Puccinia coronata f. sp. avenae). (3rd March 2019) - Admassu‐Yimer, B.; Gordon, T.; Bonman, J. M.; Esvelt Klos, K.
Abstract : Evaluation of oat crown rust resistance is usually based on visual assessment of disease severity or infection types. Visual assessment is subjective, prone to rater bias and requires expert knowledge. PCR‐based quantitative assays can overcome challenges associated with visual assessment. New TaqMan primers and probes were designed from Puccinia coronata f. sp. avenae (Pca) sequences. The primer–probe sets were specific to Pca, amplified using as little as 0.5 pg fungal DNA (fDNA) and allowed for scaling to variation in sample total DNA quantity. The quantitative PCR (qPCR) assay was validated using oat recombinant inbred lines (RILs) from the Provena × 94197A1‐9‐2‐2‐2‐5 cross evaluated under a controlled environment. For comparison with fDNA load, inoculation with the Pca race LCBB provided segregation data on the hypersensitive response, while Pca race LSLG provided data on segregation for reduced pustule number. fDNA content was positively correlated with both pustule number and infection type (IT). Composite interval mapping identified two quantitative trait loci (QTLs) on oat linkage groups Mrg12 and Mrg20 using visual and qPCR assessments (pustule number, IT and fDNA). In this study a qPCR assay method that can be used to assess the relative resistance of oat to crown rust was refined and validated, and single nucleotide polymorphisms (SNPs) closely linked with two QTLs derived from the crown rust resistant line 94197A1‐9‐2‐2‐2‐5 were identified.